Promosi Industri Fashion Clothing: Studi Deskriptif Kualitatif Promosi dalam Bentuk Web Series “Tracing Forward” pada Instagram TV @Screamous_55 - Aulia Ramadhan; Maya Amalia Oesman Palapah (UNISBA Press, 2023)
Abstract. Screamous clothing has been established since 2004 and is able to maintain its existence ntil now. To assist its promotional activities, Screamous utilizes the Instagram TV feature by making web series titled “Tracing Forward”. The series consist of 8 episodes and air on Instagram TV. This web series is specially made for followers or viewers who are 17-34 years old on average. The purpose of this research is to find out how the concept, implementation, obstacles and evaluation of the promotional activities. This study employs a qualitative method with a descriptive study approach. The data were collected through interviews, observations, documentations and literature review. The results of this study describe the implementation of promotions carried out by Screamous clothing on Instagram by utilizing the Instagram TV feature through the web series